KAJIAN PEMBELAJARAN KARYA SENI RUPA ANYAMAN PADA SISWA SEKOLAH DASAR NEGERI NEGLASARI KECAMATAN CIATER KABUPATEN SUBANG - Sari, Ika Mustika; Julia, Julia; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
This research is based on the researcher's interests in the woven learning process done to the students, because in general the learning of making webbing requires a level of rigor that is rarely owned by students of primary school age. This study aims to examine the learning process of wicker art And to know the factors that support the achievement through the learning process of webbing. The method used is qualitative research with descriptive analytic design. Data analysis techniques used are data analysis techniques based on Miles and Huberman models. This research was conducted at SDN Neglasari Sub District Ciater Subang. The result of the research is a study of the learning process of woven and the exposure of factors that support the achievement of achievement in SDN Neglasari. The supporting factor consists of two factors, Namely internal factors and external factors.